An Update on the Premerger Notification Program in the United States - GRECO, Anthony J. (Journal of Advanced Research in Law and Economics, 2017)
The United States (US) Premerger Notification program was established by the Hart-Scott-Rodino Antitrust Improvements Act of 1976 and became operative in late 1978. This Act amended the Clayton Act to require the reporting of certain planned transactions to the US Antitrust agencies prior to their consummation. Amendments of 2001 to the threshold reporting requirements, among other things, lowered the number of proposed transactions that need be reported to the antitrust agencies. This article discusses the various features and changes in the HSR program and examines the record of compliance and effectiveness of the program since its inception.